ChemInform Abstract: Palladium‐Catalyzed Synthesis of Mono‐ and Diphosphorylated 1, 10‐Phenanthrolines. Issue 18 (11th April 2013) - Mitrofanov, Alexandre; Lemeune, Alla Bessmertnykh; Stern, Christine; Guilard, Roger; Gulyukina, Nataliya; Beletskaya, Irina
Abstract The target compounds are of interest as ligands and synthons in material science.